2017
DOI: 10.1093/aobpla/plx011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deer on the photosynthetic performance of invasive and native forest herbs

Abstract: The notion that deer can facilitate plant invasions has been increasingly appreciated but the mechanisms remain unclear. In a deciduous forest stressed by overabundant deer and plant invasions, midsummer understory light levels were lower in fenced areas where deer were excluded. Further, invasive garlic mustard (Alliaria petiolata) exhibited 50% higher maximum photosynthetic rates in areas where deer were present. This trend was similar in one native (Maianthemum racemosum) while another native (Trillium gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…where A n is net assimilation rate (μmol CO 2 m −2 s −1 ), Φ is the initial quantum yield (mol CO 2 mol photons −1 ), PAR is the photosynthetic photon flux density (μmol photons m −2 s −1 ), A max is the maximum photosynthetic rate (μmol CO 2 m −2 s −1 ), θ is a dimensionless curvature parameter, and R d is daytime respiration (μmol CO 2 m −2 s −1 ). The parameters were estimated using non-linear least squares regression in R 3.5.1 (R Core Team, 2018) with code from (Heberling, Brouwer, & Kalisz, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…where A n is net assimilation rate (μmol CO 2 m −2 s −1 ), Φ is the initial quantum yield (mol CO 2 mol photons −1 ), PAR is the photosynthetic photon flux density (μmol photons m −2 s −1 ), A max is the maximum photosynthetic rate (μmol CO 2 m −2 s −1 ), θ is a dimensionless curvature parameter, and R d is daytime respiration (μmol CO 2 m −2 s −1 ). The parameters were estimated using non-linear least squares regression in R 3.5.1 (R Core Team, 2018) with code from (Heberling, Brouwer, & Kalisz, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These disturbances can influence plant invasion success in forests (e.g., Vavra et al 2007;Nuzzo et al 2009;Liu et al 2016). For example, Heberling et al (2017a), found that both light levels and photosynthetic rates of the ENA herbaceous forest invader, A. petiolata (garlic mustard), are significantly higher for plants growing in areas where deer have free access relative to fenced areas where deer are excluded. Through their effects on leaf litter and belowground dynamics, Nuzzo et al (2009) found invasive earthworms facilitate the ENA forest herb invaders, A. petiolata and the grass M. vimineum, as well as native species composition.…”
Section: Biogeographic Patterns In Understory Herbaceous Invasionsmentioning
confidence: 99%
“…Here, we focus on Alliaria petiolata (Brassicaceae, hereafter garlic mustard), Odocoileus virginianus (Cervidae, white‐tailed deer, hereafter deer), and Trillium erectum (Trilliaceae, hereafter Trillium ). Garlic mustard is a highly successful allelochemical‐producing biennial herb that diminishes the abundance of fungal hyphae in the soil (Cantor, Hale, Aaron, Traw, & Kalisz, ), the function of root‐fungal symbionts (RFS) in the soil (Callaway et al, ), and reduces the physiological performance of RFS‐dependent plants (Brouwer et al, ; Hale et al, ; Heberling, Brouwer, & Kalisz, ; Rodgers, Stinson, & Finzi, ). This mechanism, rather than competition, is commonly recognized as the process underpinning its invasive success (Brouwer et al, ; Rodgers et al, ).…”
Section: Introductionmentioning
confidence: 99%